Holistic regulation of the diabetic osteo-microenvironment via NIR-II nanocarriers with dual NO/pH responsiveness for enhanced bone regeneration - Xudong Xie; Junli Yang; Chong Ding; Yiming Li; Fawwaz Ai-Smadi; Kangkang Zha; Chuanlu Lin; Ze Lin; Chenyan Yu; Ruiyin Zeng; Weixian Hu; Jiewen Liao; et al. (Bioactive Materials)
Diabetic conditions impair bone regeneration due to dysregulated macrophage polarization and inflammatory imbalance. Current therapies often fail to address systemic immune homeostasis. Herein, a bone-targeted nanoplatform (abbreviated as AgSr-MSNs) is engineered to scavenge excess nitric oxide (NO) and respond to the acidic diabetic microenvironment based on upregulated inducible nitric oxide synthase (iNOS) expression in M1 macrophages residing within both the diabetic bone marrow and localized osteolytic regions in our study. The system integrates silver sulfide quantum dots (Ag2S QDs) and Sr2+ into mesoporous silica nanoparticles (MSNs), encapsulated with rhodamine/β-cyclodextrin and surface-modified with alendronate for bone-specific targeting. Under near-infrared (NIR) irradiation, the nanoparticles induce macrophage repolarization toward M2 phenotypes through JAK/STAT signaling pathway, followed by upregulating anti-inflammatory mediators (TGF-β, PD-L1) and tissue-regenerative factors (BMP-2/4, VEGF-B), while suppressing pro-inflammatory cytokines (CCR2, S100A4). This dual NO/pH-responsive platform synergistically mitigates inflammatory dysregulation, enhances osteogenesis, and promotes angiogenesis. In diabetic models, systemic administration with NIR-mediated mild hyperthermia reduces CD86+ macrophages and TNF-α levels while elevating CD206+ macrophages locally and systemically. Concurrently, it boosts CD31, Runx2, and osteocalcin (OCN) expression levels at defect sites, indicating restored vascularization and osteogenesis. This strategy addresses the pathological triad of diabetic osteopathy—chronic inflammation, vascular insufficiency, and osteogenic impairment—providing a translatable nanotherapeutic paradigm for metabolic bone disorders.